2023
DOI: 10.1186/s12964-023-01243-9
|View full text |Cite|
|
Sign up to set email alerts
|

Human Parathyroid Hormone Analog (3–34/29–34) promotes wound re-epithelialization through inducing keratinocyte migration and epithelial–mesenchymal transition via PTHR1-PI3K/AKT activation

Chunhao Zhou,
Donghua Guan,
Jialiang Guo
et al.

Abstract: Background Re-epithelialization is important in the process of wound healing. Various methods have been identified to expedite the process, but their clinical application remains limited. While parathyroid hormone (PTH) has shown promising results in wound healing due to its role in promoting collagen deposition and cell migration, application is limited by its potentially inhibitive effects when being continuously and locally administrated. Herein, we developed a novel PTH analog, Human parath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To verify whether the protein loaded in Neuro-MOF induces EMT, we selected human immortalized keratinocytes (HaCaT cells) treated with Neuro-MOF to test their EMT, proliferation, and migration capabilities. It is a commonly used cellular model for examining the EMT of keratinocytes during skin wound healing. As shown in Figure d–f, fibronectin and Vimentin, as markers of EMT, are significantly upregulated under the action of Neuro-MOF, whether in fluorescent confocal observation or Western blotting. It confirms the effect of Neuro-MOF on the induction of EMT in HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
“…To verify whether the protein loaded in Neuro-MOF induces EMT, we selected human immortalized keratinocytes (HaCaT cells) treated with Neuro-MOF to test their EMT, proliferation, and migration capabilities. It is a commonly used cellular model for examining the EMT of keratinocytes during skin wound healing. As shown in Figure d–f, fibronectin and Vimentin, as markers of EMT, are significantly upregulated under the action of Neuro-MOF, whether in fluorescent confocal observation or Western blotting. It confirms the effect of Neuro-MOF on the induction of EMT in HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it also exerts effects on angiogenesis and extracellular matrix (ECM) deposition [ 4 , 12 , 13 ]. However, the definitive role of hPTH(1–34) in skin-wound healing and the underlying mechanisms remain unclear, although a few studies reported that PTH or PTH analogs (PTHrP2 and MY-1) led to a quicker wound closure [ 4 , 14 16 ]. To date, although the in-vivo application of PTH has been under-reported, there is a paucity of detailed experiments that demonstrate the definitive effects of PTH on fibroblasts and keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors wish to clarify their affiliations. The affilaitions in this correction article are displayed correctly (specifically affiliation 1 and 3).…”
mentioning
confidence: 99%